Implementation and performance of a taste sensing system for quality assessment of agrobased products - Abdul Hallis, Abdul Aziz (Universiti Malaysia Perlis (UniMAP), 2012)
The trend in human food consumption is seeing a shift in demand, from consumer’s side demanding increase of health elements in food and from manufacturer’s side demanding higher palatability. Currently, quality of farm production is not verifiable and its quality claim is very dependent on farmers very own personal validation and rationale made by selected human panelist. Laboratory verification on the other hand, is cost prohibitive, requires trained labor to operate and yet does not indicate taste, which is a mixture of chemicals. This thesis presents the design, characterization and performance analysis of a taste sensing system (TSS) in assessing the quality of agro-based products. The system integrates off-the-shelf components to incorporate simplicity in reproducing the system while maintaining affordable cost. Operation interface is presented as graphical user interface (GUI) to allow operation by non-technical personnel in other discipline. The TSS exhibit exceptional ability (above 80%) in discriminating quantitative taste samples and perfect (100%) discrimination of qualitative samples.